2017
DOI: 10.24873/j.rpemd.2017.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Estado de saúde oral duma população institucionalizada com deficiência profunda

Abstract: Avaliar o estado de saúde oral de uma população institucionalizada com deficiência profunda e averiguar a sua relação com potenciais fatores determinantes. Métodos: A população-alvo consistiu nos residentes do Centro de Apoio a Deficientes Profundos Luís da Silva (Borba). A recolha de dados foi realizada através de exame intraoral e aplicação de um questionário aos cuidadores responsáveis pela higiene oral dos residentes. Foram avaliados o índice CPOD, o índice gengival e o índice de higiene oral simplificado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…erefore, a lot remains to be achieved by the society with (1) Difficult to take time off from work to bring child to the dentist (2) Difficult to find dentist willing to treat child because of their medical condition (3) Dental care is very expensive (4) Difficult to find a child dentist nearby (5) Difficult to travel to the dental office (6) e dental team is anxious or nervous treating children (7) Child is afraid of the dentist (8) Child does not like to do anything to his mouth (9) e child is too young to see a dentist (10) Dad is afraid to go to the dentis (11) International Journal of Dentistry regard to the facilitation of access to health care. Overcoming the barriers encountered by people with disabilities can thereby enable their much deserved and dignified access to oral health services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…erefore, a lot remains to be achieved by the society with (1) Difficult to take time off from work to bring child to the dentist (2) Difficult to find dentist willing to treat child because of their medical condition (3) Dental care is very expensive (4) Difficult to find a child dentist nearby (5) Difficult to travel to the dental office (6) e dental team is anxious or nervous treating children (7) Child is afraid of the dentist (8) Child does not like to do anything to his mouth (9) e child is too young to see a dentist (10) Dad is afraid to go to the dentis (11) International Journal of Dentistry regard to the facilitation of access to health care. Overcoming the barriers encountered by people with disabilities can thereby enable their much deserved and dignified access to oral health services.…”
Section: Resultsmentioning
confidence: 99%
“…In South Korea, researchers evaluated comparable samples of people (a) with physical disabilities (DMFT � 7.3), (b) with mental disabilities (DMFT � 8.3), and (c) with multiple disabilities (DMFT � 8.2) and people without disabilities (DMFT � 4.9) [6]. In another study carried out in Portugal, with institutionalized people with disabilities, a mean DMFT of 11.2 was found which was much higher than the general population of the same age group [7]. In Brazil, in a study carried out with people with Down syndrome, cerebral palsy, and intellectual deficit, the average DMFT was 11.0, also quite high when compared to the general population of the same age group [8].…”
Section: Introductionmentioning
confidence: 94%
“…The most used index to assess caries risk is the DMF/T index (D, decayed; M, missing; F, filled; T, teeth). Epidemiological studies show significantly higher DMF/T values in PIMD [8][9][10], and PIMD still has more missing teeth than the general population [11].…”
Section: Introductionmentioning
confidence: 92%
“…Regarding the degree of independence in performing dental hygiene, the study by Esteves et al (2017) found that people with special needs that are more dependent had better oral health status. This result, according to the authors, can be justified by the fact that third parties perform the oral hygiene of the person with special needs more effectively.…”
Section: Theoretical Frameworkmentioning
confidence: 99%